2015
DOI: 10.1371/journal.pone.0118140
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Bacterium Bacteroides thetaiotaomicron Influences the Virulence Potential of the Enterohemorrhagic Escherichia coli O103:H25

Abstract: Enterohemorrhagic E. coli (EHEC) is associated with severe gastrointestinal disease. Upon entering the gastrointestinal tract, EHEC is exposed to a fluctuating environment and a myriad of other bacterial species. To establish an infection, EHEC strains have to modulate their gene expression according to the GI tract environment. In order to explore the interspecies interactions between EHEC and an human intestinal commensal, the global gene expression profile was determined of EHEC O103:H25 (EHEC NIPH-11060424… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…A further exploration of the interactions between E. coli O157:H7 and the plethora of bacterial species present in the gut is needed to appreciate how the gut microbiome affects the virulence of this foodborne pathogen. It was also shown previously that fecal Bacteroides thetaiotaomicron alters Stx2 expression (40)(41)(42), although two studies (40,42) report decreases while one (41) report shows Hematoxylin-and eosin-stained renal sections from mice infected with either C600 or PA2 and PA2 plus C600. The mice were scored as described in Materials and Methods.…”
Section: Figmentioning
confidence: 63%
“…A further exploration of the interactions between E. coli O157:H7 and the plethora of bacterial species present in the gut is needed to appreciate how the gut microbiome affects the virulence of this foodborne pathogen. It was also shown previously that fecal Bacteroides thetaiotaomicron alters Stx2 expression (40)(41)(42), although two studies (40,42) report decreases while one (41) report shows Hematoxylin-and eosin-stained renal sections from mice infected with either C600 or PA2 and PA2 plus C600. The mice were scored as described in Materials and Methods.…”
Section: Figmentioning
confidence: 63%
“…This is mediated by inhibition of the lytic cycle via the SOS response regulator RecA. Interestingly, similar results were obtained when EHEC O157:H7 was cultured in medium conditioned by the predominant species of the Bacteroides phylum B. thetaiotaomicron only [108,118]. Furthermore, Cordonnier and colleagues demonstrated that reduced Stx2 production was dependent on internalization of vitamin B 12 by B. thetaiotaomicron as a mutant deficient in an outer membrane receptor of vitamin B 12 was unable to repress the Stx2 production.…”
Section: Effect Of Biotic or Host Cell-related Parametersmentioning
confidence: 59%
“…Several studies have shown that Lactobacillus and Bifidobacterium species decrease EHEC adhesion to intestinal epithelial cells in vitro by different mechanisms including direct competition for binding sites at the enterocyte surface [97,98,99,100,101], production of molecules modulating expression of adhesins [102,103,104] and stimulation of mucus production, thereby preventing access to the epithelial surface [105,106]. Conversely, in vitro co-culture of EHEC O157:H7 and O103:H25 and the commensal strain Bacteroides thetaiotaomicron led to increased expression of all LEE operons [107,108], increased epithelial adhesion and formation of A/E lesions. The same effect was observed following co-incubation of EHEC O157:H7 and Enterococcus faecalis , a commensal strain belonging to the phylum Firmicutes [107].…”
Section: Effect Of Biotic or Host Cell-related Parametersmentioning
confidence: 99%
“…Bacteroides tethaiotaomicron , a predominant member of the gut microbiota in healthy subjects, enhanced the expression of several genes of STEC reference strain in co-culture experiments, including virulence genes located in the LEE pathogenicity island. Moreover, an increase of A/E lesions and STEC adherence to epithelial cells was found (Curtis et al, 2014 ; Iversen et al, 2015 ). Considering the above, further studies should focus on the role of species described here as indicative of DEC group in the pathogenicity of DEC pathotypes.…”
Section: Discussionmentioning
confidence: 99%
“…However, this phenomenon is not completely understood for DEC, as most studies have focused on molecular mechanism occurring inside the bacteria, with only a few evaluating environmental factors, such as, gut microbiota (Pacheco and Sperandio, 2015 ; Singh et al, 2015 ). In the last years, several groups have focused on the role components of the gut microbiota and its association with diarrheal disease caused by enteric pathogens, including DEC strains (Nelson et al, 2012 ; Curtis et al, 2014 ; Iversen et al, 2015 ; Lindsay et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%